2019
DOI: 10.1002/anie.201906971
|View full text |Cite
|
Sign up to set email alerts
|

Access to FeII Bis(σ‐B−H) Aminoborane Complexes through Protonation of a Borohydride Complex and Dehydrogenation of Amine‐Boranes

Abstract: Herein, we report on the first synthesis and structural characterization of the iron based aminoborane complexes [Fe(PNP)(H)(η2:η2‐H2B=NR2)]+ (R=H, Me). These species are formed upon protonation of the borohydride complex [Fe(PNP)(H)(η2‐BH4)] by ammonium salts [NH2R2]+ (R=H, Me). For R=Me, the reaction proceeds via the cationic dinuclear intermediate [{Fe(PNP)(H)}2(μ2,η2:η2‐BH4)]+. A mechanism for the reaction is proposed based on DFT calculations that also indicate the final aminoborane complex as the thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…In contrast, dissociation of the aminoborane ligand in 2 under an atmosphere of dihydrogen to form 3 was not be observed. 15 The hydrogenation of A1 was conducted at different hydrogen pressures as well as substrate concentrations and the initial turnover frequencies were determined after a reaction time of five minutes. A significant increase of the initial TOFs could be observed at higher hydrogen pressures (see supporting information, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, dissociation of the aminoborane ligand in 2 under an atmosphere of dihydrogen to form 3 was not be observed. 15 The hydrogenation of A1 was conducted at different hydrogen pressures as well as substrate concentrations and the initial turnover frequencies were determined after a reaction time of five minutes. A significant increase of the initial TOFs could be observed at higher hydrogen pressures (see supporting information, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies revealed that the hydrogenation initially affords (Z)-alkenes which, however, are isomerized to the respective (E)-olefins by the same catalyst. We describe here the application of the well-defined bench-stable cationic aminoborane complex [Fe(PNP NMe -iPr)(H)(η 2 -H2B=NMe2)] + (2) described recently 15 as highly efficient pre-catalysts for the semi-hydrogenation of internal alkynes, 1,3diynes and 1,3-enynes with molecular hydrogen under mild conditions. We take advantage of the fact that the aminoborane ligand, which is coordinated to the metal center via two weak σ-B-H bonds in η 2 -fashion, is substitutionally labile and upon dissociation readily provides two vacant coordination sites to bind dihydrogen and alkynes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, 11 and others, 24 have recently commented on the role of amine in promoting catalytic turnover in a variety of dehydrocoupling systems; and there is a very recent complementary report of the stoichiometric role of ammonium/amine in the protonation of borohydride complexes to eventually form σ-bound aminoboranes. 92 In the system under discussion here the amine-assisted formation of the neutral hydride, i.e. 4, and [NMe 2 H 2 ] + is rate limiting in catalysis, although this may not necessarily be the case for every system in a more general sense.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous transition-metal-mediated reactions have been developed based on the design and synthesis of appropriate catalysts [30][31][32]. Among these, iron-based catalysts represent some of the most promising candidates for the development of practical systems owing to their low cost, earth-abundance, and low toxicity [33][34][35][36][37][38][39][40][41][42]. Thus, great efforts have been devoted to developing iron-mediated reactions for the dehydrogenation of ammonia borane derivatives.…”
Section: Catalytic Dehydrogenation Of Ammonia Borane Catalysed Bymentioning
confidence: 99%